PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN CURRENT RATIO TERHADAP HARGA SAHAM PERIODE 2019 - KUARTAL KEDUA TAHUN 2023 - Lim, Calvin Sukma Pegasus (SCIENTIA JOURNAL, 2024)
This study was conducted to examine the effect of ROA, EPS, and CR on Stock Price for the period 2019 – second quarter of 2023. The study tested nine manufacturing companies listed on the LQ45 index during the period 2019 - the second quarter of 2023. Data collection techniques in this study use documentation studies and literature studies with purposive sampling techniques as sampling techniques. The type of data used is secondary data in the form of financial statements obtained from the Indonesia Stock Exchange website. The analysis method used is multiple linear regression analysis and uses classical assumption tests including normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests. Other tests used in this study are multiple linear regression tests and hypothesis tests using t tests (partial tests), f tests (simultaneous tests), and multiple coefficients of determination with the help of the SPSS program version 26. The conclusion in this study is that the t test states that partially EPS (Earning Per Share) affects stock price while ROA (Return On Assets) and CR (Current Ratio) do not affect stock price partially and based on test f simultaneously the variables ROA, EPS, and CR affect stock price